Simultaneous separation and sensitive detection of four β2-agonists in biological specimens by CE-UV using a field-enhanced sample injection method. Issue 1 (26th November 2014) - Chen, Cheng; Meng, Lingchen; Li, Meixian; Zhu, Zhiwei
Abstract : A rapid, sensitive and cost-effective CE-UV method has been developed for the simultaneous separation and sensitive determination of four beta2-agonists. Abstract : A rapid, sensitive and cost-effective CE-UV method has been developed for the simultaneous separation and sensitive determination of clenbuterol, salbutamol, ractopamine and fenoterol in pig blood and human urine samples. Field-enhanced sample injection (FESI) as an effective online concentration technique was applied to improve the detection sensitivity of β2-agonists. Several factors, such as the concentration and pH of the background solution, sample matrix, injection time and voltage, and the length of the water plug, were systematically optimized. Under the optimum conditions, the detection limits of the β2-agonists range from 2.7 to 7.2 nM, which were improved nearly 2000 times by CE-UV compared with conventional methods, except for fenoterol. Eventually, the proposed method was successfully applied to the analysis of spiked blood and urine samples with good recoveries, which provides a novel method to monitor the illegal use of β2-agonists in athletes and livestock.